2011
DOI: 10.1111/j.1462-2920.2011.02583.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of putative biocorroding microbiota with a novel niche detection of Epsilon‐ and Zetaproteobacteria in Pacific Ocean coastal seawaters

Abstract: Submerged metal surfaces in marine waters undergo rapid microbial colonization and biocorrosion, causing huge damage to marine engineering facilities and significant financial losses. In coastal areas, an accelerated and particularly severe form of biocorrosion termed accelerated low water corrosion (ALWC) is widespread globally. While identification of biocorroding microorganisms and the dynamics of their community structures is the key for understanding the processes and mechanisms leading to ALWC, neither o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
93
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 88 publications
(144 reference statements)
7
93
0
Order By: Relevance
“…This difference in diversity may not only be due to PCR primer coverage and specificity but also may result from some experimental details that might improve the quality of our experiment (Dang et al 2008c;Li et al 2010). Indeed, some of the sediment bacterial groups uniquely found in the current study were also detected in previous surface-colonizing bacterial community analyses in Qingdao coastal seawater (Dang et al 2008a(Dang et al , 2011. In the present study, the Power Soil DNA Extraction Kit was used, which has been demonstrated to be an efficient DNA extraction method for marine sediments.…”
Section: Bacterial Taxonomic Diversity In Jiaozhou Bay Sedimentsmentioning
confidence: 53%
See 1 more Smart Citation
“…This difference in diversity may not only be due to PCR primer coverage and specificity but also may result from some experimental details that might improve the quality of our experiment (Dang et al 2008c;Li et al 2010). Indeed, some of the sediment bacterial groups uniquely found in the current study were also detected in previous surface-colonizing bacterial community analyses in Qingdao coastal seawater (Dang et al 2008a(Dang et al , 2011. In the present study, the Power Soil DNA Extraction Kit was used, which has been demonstrated to be an efficient DNA extraction method for marine sediments.…”
Section: Bacterial Taxonomic Diversity In Jiaozhou Bay Sedimentsmentioning
confidence: 53%
“…Besides SRB, potential sulfuroxidizing bacteria (SOB), which belong to ε-, γ-, and α-subdivision of Proteobacteria also constitute an important fraction in bacterial communities of marine sediments (Zeng et al 2009). Similar SOB sequences have also been detected abundantly in the surfaces of submerged carbon steel coupons in Qingdao coastal seawater (Dang et al 2011). In the eastern part of the Jiaozhou Bay, increasing nutrient input due to intensive agriculture and industry causes serious eutrophication, which may be related to the high levels of δ-and ε-Proteobacteria in the A5 station.…”
Section: Bacterial Communities In Comparable Habitsmentioning
confidence: 77%
“…To date, the Zetaproteobacteria have only been identified in habitats with high ferrous iron concentrations. Within this context, they have been detected in a wide range of environments from hydrothermal vent sites, such as Loihi Seamount, where they can dominate the microbial community (Rassa et al, 2009;Emerson and Moyer, 2010;McAllister et al, 2011;Fleming et al, 2013), to coastal environments, where they may be involved in biocorrosion of steel structures such as ships and pilings (Dang et al, 2011;McBeth et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The result of these processes is the need for more frequent maintenance of structures, such as piers, bridges, and pipelines, as well as an increased risk of catastrophic failure. The majority of the existing literature suggests that MIC is primarily a result of surface colonization by sulfate-reducing bacteria (SRB) (2-26), and while it is clear that the SRB play a major role in MIC, recent reports (2,3,15,17,27,28) have demonstrated the presence of lithotrophic Fe-oxidizing bacteria (FeOB) on steel surfaces impacted by MIC. FeOB utilize Fe(II) released from the steel surface as their primary energy source and are autotrophic, requiring only a few micronutrients in addition to Fe(II) to grow (29).…”
mentioning
confidence: 99%
“…As a result, they are well suited to be early colonizers of steel. Several studies have shown that during in situ incubations of mild steel, FeOB are capable of early colonization, and this pioneering colonization is followed by an increase in diversity of the surface community, including development of SRB populations (3,17,27). The FeOB that naturally colonize either mineral or steel surfaces are known to produce porous mats comprised of interwoven stalks of polysaccharides and poorly crystalline iron oxyhydroxides (17,23,28,30,31).…”
mentioning
confidence: 99%